(untitled) (American Journal of Islam and Society, 1991)
Griffin’s larger program in God and Religion in the Postmodern World is to develop a process theology able to meet the challenges and opportunities presented by science and modernity. This process theology draws extensively on the work of Whitehead and Hartshorne and essentially entails destroying modernity as an ideology while retaining certain parts of the scientific worldview, returning to some aspects of premodernity (such as the view of enchanted nature), and creating a holistic, pluralistic, dynamic view of the nature of God and humanity. Besides this program, Griffin develops a number of insightful ideas. Getting around the problem of describing a phenomenon like postmodernism, which wants to preclude all closure and definition, Griffin makes the case that destructive postmodemism is really ultramodernism, modernism carried to its logical conclusion. This avoids the confusion of "constructive" postmodern thought. Griffin also makes the case for panentheism, as opposed to pantheism or the absolute dichotomy popular two or more centuries ago among Christian theologians. Throughout the book, Griffin puts forward many original and insightful ways of looking at Western thought, Christian theology, and the rise of modernism. These insights deserve to be explored; they certainly should stimulate fruitful discussion. The major problem of Griffin’s work for the Muslim is his desire, and that of process theologians as a whole, to create a new religion. Huston Smith addresses this issue in a forthcoming work where the two debate this and other issues. (I look forward to reading this book.) Griffin is not sufficiently aware of the perennial perspective, which makes me predict that Huston Smith will offer quite persuasive arguments against process theology. This perspective holds that no meaningful religious experience can take place without a grounding and foundation in a divinely revealed tradition. Islam has been completed and protected by Allah Himself in the form of the Qur’an and the Sunnah, and so we need not create a new religion to appreciate premodernity or to destroy modernity. It is the task of Islamic scholars to engage the issues Griffin brings up, a project which will surely lead us to rediscover ideas and processes in our heritage which may be fruitfully ...